The Effect of Using Flashcards During Online Learning Towards Speaking Skills at 11th Grade Social Class at Mutiara Bangsa 2 School - Nina Susanti; Supeno Supeno; Nina Dwiastuty (JEdu: Journal of English Education, 2022)
The purpose of this research is to discuss the effect of flashcards on teaching speaking. The purpose of this research is to find out whether Flashcard is effective for teaching speaking during online learning. This study used a quasi-experimental method with a one group pre-test and post-test design. There are two variables in this study; namely the independent variable and the dependent variable, while the independent variable is Flashcard and the dependent variable is the result of the post test (students' speaking ability). The population in this study were students of class XI Mutiara Bangsa 2. The sample of this study amounted to 13 people. This study uses only one instrument. It is an oral speaking test. Furthermore, the process instrument was used pre-test and post-test. In addition, the researcher collected data by assessing students' vocabulary and fluency. As a result, the data showed that there was a significant difference between the post-test students in the experimental class and the control class. The post-test P-value is lower than the significance level which indicates that there is a significant difference between the pre-test and post-test mean.